Serotonergic drug repurposing in multiple sclerosis: A new possibility for disease-modifying therapy - Melnikov, Mikhail; Kasatkin, Dmitriy; Lopatina, Anna; Spirin, Nikolay; Boyko, Alexey; Pashenkov, Mikhail (Frontiers in Neurology, 2022)
Investigation of neuroimmune interactions is one of the most developing areas in the study of multiple sclerosis pathogenesis. The recent evidence suggests the possibility of modulating neuroinflammation by targeting biogenic amine receptors. It has been shown that selective serotonin reuptake inhibitor fluoxetine modulates innate and adaptive immune system cells' function and can reduce experimental autoimmune encephalomyelitis and multiple sclerosis severity. This brief report discusses the immune mechanisms underlying the multiple sclerosis pathogenesis and the influence of fluoxetine on them. The retrospective data on the impact of fluoxetine treatment on the course of multiple sclerosis are also presented. The results of this and other studies suggest that fluoxetine could be considered as additional therapy to the standard first-line disease-modifying treatment for relapsing-remitting multiple sclerosis.